Impact of routinely employed procedures for tissue processing on the proteomic analysis of formalin‐fixed paraffin‐embedded tissue. Issue 10 (24th July 2014) - Bronsert, Peter; Weißer, Juliane; Biniossek, Martin L.; Kuehs, Markus; Mayer, Bettina; Drendel, Vanessa; Timme, Sylvia; Shahinian, Hasmik; Küsters, Simon; Wellner, Ulrich F.; Lassmann, Silke; Werner, Martin; et al.
<x xml:space="preserve">Abstract</x> Purpose FFPE (formalin fixed, paraffin embedded) tissue cohorts represent an enduring archive of clinical specimens. Proteomic analysis of FFPE tissues is gaining interest for the in‐depth analysis of aberrant proteome composition. Procedures for FFPE tissue processing are standardized but there is diversity regarding the different processing systems. This work focuses on three different processing methods commonly used in large European pathology institutes. Experimental design Formalin fixed tissue specimens of different tumors were serially sliced and processed with three different processing systems (xylene, ethanol/vacuum or microwave based). After paraffin embedding, they were subjected to MS‐based proteomic analysis to investigate the impact of tissue processing techniques on the quality of proteomic analysis. Results were compared with proteomic analysis of corresponding cryopreserved tissue specimens. Results All processing techniques achieved very good proteome coverage similar to the cryopreserved counterpart. Gene ontology profiles, relative protein abundances, and peptide modifications such as methionine oxidation or proteolytic truncation were highly similar for all techniques as well as for the cryopreserved samples. Conclusions and clinical relevance The results show that different processing procedures do not impede proteomic analysis as a robust and powerful approach for the identification of protein determinants and markers of disease processes and highlights the general robustness of FFPE‐tissue based proteomics.